웹 컴포넌트의 내부 구조를 활용한 마이크로서비스 자동 식별 - Si-Hyun Kim(김시현); Jae-Hyuk Shin(신재혁); Jaewon Oh(오재원) (한국정보통신학회논문지, 2023)
Automatic identification of microservices in legacy webapps has attracted considerable attention, leading to theproposal of various approaches to address this problem. Someof the proposed approaches focus on the words that make upweb apps. This paper proposes a novel approach that utilizesthe context in which words appear in web components. To thisend, a neighbor relationship between words is defined andextracted in terms of the hierarchical structure of a webcomponent. Then web components are embedded using theneighbor relationships and classified into appropriatemicroservices. Experiments are conducted using open-sourceweb apps to validate the proposed approach. KCI Citation Count: 1